A presentation of scientific research programs proposed by Lakatos base don the Alfa Beta method: An approach economic science - Cisneros García, Juan Manuel (2017)
We present Lakatos’s epistemological approach concerning scientific research programs regarding alpha beta method. We focus on Economic Science, for that we propose a set of auxiliary assumptions for expressing the lakatosian notions: hard core (as a finite set of some similar α propositions of some theories) and protective belt (propositions a); heuristics and auxiliary assumptions incorporated allow us to operationalize a scientific research program therefore can be empirically tested.